The handbook of hybrid securities : convertible bonds, coco bonds, and bail-in - Spiegeleer, Jan de (John Wiley Sons, 2014)
"Introducing a revolutionary new quantitative approach to hybrid securities valuation and risk managementTo an equity trader they are shares. For the trader at the fixed income desk, they are bonds (after all, they pay coupons, so what's the problem?). They are hybrid securities. Neither equity nor debt, they possess characteristics of both, and carry unique risks that cannot be ignored, but are often woefully misunderstood. The first and only book of its kind, The Handbook of Hybrid Securities dispels the many myths and misconceptions about hybrid securities and arms you with a quantitative, practical approach to dealing with them from a valuation and risk management point of view. Describes a unique, quantitative approach to hybrid valuation and risk management that uses new structural and multi-factor models Provides strategies for the full range of hybrid asset classes, including convertible bonds, preferreds, trust preferreds, contingent convertibles, bonds labeled "additional Tier 1," and more Offers an expert review of current regulatory climate regarding hybrids, globally, and explores likely political developments and their potential impact on the hybrid market The most up-to-date, in-depth book on the subject, this is a valuable working resource for traders, analysts and risk managers, and a indispensable reference for regulators "--